Trajectory planning algorithm for merging control of heterogeneous vehicular platoon on curve road - Bian, Chentong; Yin, Guodong; Xu, Liwei; Zhang, Ning (Transport, 2022)
The main goal of this study is to propose a trajectory planning algorithm for the merging control of heterogeneous vehicular platoons. Merging control is essential for the application of vehicular platoons, by which vehicles can be coordinated to form a platoon in a lane. While most previous researches on merging control only considered the operation on straight roads and ramps. Few studies have investigated the merging operation on curve roads, which may hinder the application of platoons on general traffic environment. In this study, a trajectory planning algorithm is proposed for the merging control of heterogeneous vehicular platoons on curve roads with constant radius. The proposed algorithm consists of two stages for the operation of merging: the first stage is to align the vehicles in each lane to form a structure with a certain clearance; the second stage is to conduct a lane changing manoeuvre for each merging vehicle to form a platoon in a lane. In the proposed algorithm, the dynamic limits of speed and acceleration are considered. The distance of each vehicle can be guaranteed to avoid undesired collisions. Two simulations are carefully conducted for the merging control of heterogeneous vehicular platoons on a curve road to demonstrate the effectiveness of the proposed algorithm. The results of simulations indicate that the proposed algorithm is capable of the merging control of platoons on a curve road.